Identification of a New Lipoprotein Export Signal in Gram-Negative Bacteria - Frédéric Lauber (American Society for Microbiology, 2016)
ABSTRACT Bacteria of the phylum Bacteroidetes, including commensal organisms and opportunistic pathogens, harbor abundant surface-exposed multiprotein membrane complexes (Sus-like systems) involved in carbohydrate acquisition. These complexes have been mostly linked to commensalism, and in some instances, they have also been shown to play a role in pathogenesis. Sus-like systems are mainly composed of lipoproteins anchored to the outer membrane and facing the external milieu. This lipoprotein localization is uncommon in most studied Gram-negative bacteria, while it is widespread in Bacteroidetes. Little is known about how these complexes assemble and particularly about how lipoproteins reach the bacterial surface. Here, by bioinformatic analyses, we identify a lipoprotein export signal (LES) at the N termini of surface-exposed lipoproteins of the human pathogen Capnocytophaga canimorsus corresponding to K-(D/E)2 or Q-A-(D/E)2. We show that, when introduced in sialidase SiaC, an intracellular lipoprotein, this signal is sufficient to target the protein to the cell surface. Mutational analysis of the LES in this reporter system showed that the amino acid composition, position of the signal sequence, and global charge are critical for lipoprotein surface transport. These findings were further confirmed by the analysis of the LES of mucinase MucG, a naturally surface-exposed C. canimorsus lipoprotein. Furthermore, we identify a LES in Bacteroides fragilis and Flavobacterium johnsoniae surface lipoproteins that allow C. canimorsus surface protein exposure, thus suggesting that Bacteroidetes share a new bacterial lipoprotein export pathway that flips lipoproteins across the outer membrane. IMPORTANCE Bacteria of the phylum Bacteroidetes are important human commensals and pathogens. Understanding their biology is therefore a key question for human health. A main feature of these bacteria is the presence of abundant lipoproteins at their surface that play a role in nutrient acquisition. To date, the underlying mechanism of lipoprotein transport is unknown. We show for the first time that Bacteroidetes surface lipoproteins share an N-terminal signal that drives surface localization. The localization and overall negative charge of the lipoprotein export signal (LES) are crucial for its role. Overall, our findings provide the first evidence that Bacteroidetes are endowed with a new bacterial lipoprotein export pathway that flips lipoproteins across the outer membrane.